Description of a new species of the genus Stigmaeus Koch (Acari: Stigmaeidae) from Turkey, with a list of described species in the world - Dogan, Salih; Bingul, Meryem; Dilkaraoglu, Sibel; Fan, Qing-Hai (Taylor & Francis Inc, 2015)
Stigmaeus erzincanus sp. nov. collected from soil and litter under Pinus sylvestris, Erzincan, Turkey is described and illustrated here. This species can clearly be distinguished by having apodemal marking, eyes and pob absent, one pair of extra and non-setose dorsal shields, suranal shield entire, genual setal formula 5(+1 kappa)-5-2-2, terminal eupathidion on palpal tarsus trident, IV omega present. [GRAPHICS]
Keywords: new species; Erzincan; Stigmaeus; Acari; Turkey; Raphignathoidea